Lessons from past radiation accidents: Critical review of methods addressed to individual dose assessment of potentially exposed people and integration with medical assessment. (January 2021) - Barquinero, Joan Francesc; Fattibene, Paola; Chumak, Vadim; Ohba, Takashi; Della Monaca, Sara; Nuccetelli, Cristina; Akahane, Keiichi; Kurihara, Osamu; Kamiya, Kenji; Kumagai, Atsushi; Challeton-de Vathaire, Cecile; Franck, Didier; et al.
Highlights : A detailed chronicle on dosimetry after the Chernobyl and Fukushima accidents. A critical analysis of the weak points from the previous nuclear accidents. Recommendations to improve dosimetry for decision making processes. Applications of dosimetry in medical surveillance and preventive healthcare. Abstract: The experiences of the Chernobyl and Fukushima nuclear accidents showed that dosimetry was the essential tool in the emergency situation for decision making processes, such as evacuation and application of protective measures. However, at the consequent post-accidental phases, it was crucial also for medical health surveillance and in further adaptation to changed conditions with regards to radiation protection of the affected populations. This review provides an analysis of the experiences related to the role of dosimetry (dose measurements, assessment and reconstruction) regarding health preventive measures in the post-accidental periods on the examples of the major past nuclear accidents such as Chernobyl and Fukushima. Recommendations derived from the review are called to improve individual dose assessment in case of a radiological accident/incident and should be considered in advance as guidelines to follow for having better information. They are given as conclusions.